2013
DOI: 10.1111/j.1442-200x.2012.03728.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic variability in preterm infants receiving intermittent gastric tube feeding: Report of three cases

Abstract: Late-onset hypoglycemia (day 12-16, blood glucose <50 mg/dL) was detected in three preterm infants (birthweight 998-1780 g; gestational age 27-30 weeks) by routine screening. All infants showed high serum insulin levels and extremely low ketone levels at the time of hypoglycemia. Continuous glucose monitoring was conducted at 31-34 weeks' postconceptual age when the infants were receiving intermittent gastric tube feeding with no intravenous glucose infusion. The continuous glucose monitoring results showed ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…There are existing reports of continuous glucose monitoring devices used for neonates. In Japan, only a few cases have been reported, for tube‐fed, very low birthweight infants and for hyperinsulinemic hypoglycemia 6–8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are existing reports of continuous glucose monitoring devices used for neonates. In Japan, only a few cases have been reported, for tube‐fed, very low birthweight infants and for hyperinsulinemic hypoglycemia 6–8 …”
Section: Discussionmentioning
confidence: 99%
“…In Japan, only a few cases have been reported, for tube-fed, very low birthweight infants and for hyperinsulinemic hypoglycemia. [6][7][8] We first examined the safety and accuracy of the FGM device in term neonates before using it in high-risk infants who need careful blood glucose management.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, continuous feeding may reduce feeding intolerance and improve growth . We previously suggested that continuous feeding may also be beneficial from the perspective of glycemic stability . The clinical significance of large glycemic variability regarding future complications of preterm infants, however, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we described the cases of preterm infants who had repeated abnormal glucose levels >3 weeks after birth, detected on continuous glucose monitoring (CGM). 1 CGM was initially developed to improve the metabolic control in diabetes mellitus. CGM is also useful, safe, and reliable in neonates, including infants with very low birthweight.…”
mentioning
confidence: 99%